Application of New Radiosensitizer Based on Nano-Biotechnology in the Treatment of Glioma - Xie, Yandong; Han, Yuhan; Zhang, Xuefeng; Ma, Hongwei; Li, Linfeng; Yu, Rutong; Liu, Hongmei (Frontiers in Oncology, 2021)
Glioma is the most common intracranial malignant tumor, and its specific pathogenesis has been unclear, which has always been an unresolved clinical problem due to the limited therapeutic window of glioma. As we all know, surgical resection, chemotherapy and radiotherapy are the main treatment methods for glioma. With the development of clinical trials and traditional treatment techniques, radiotherapy for glioma has increasingly exposed defects in the treatment effect. In order to improve the bottleneck of radiotherapy for glioma, people have done a lot of work, among which, nano-radiosensitizers have offered a novel and potential treatment method. Compared with conventional radiotherapy, nanotechnology can overcome the blood-brain barrier and improve the sensitivity of glioma to radiotherapy. This paper focuses on the research progress of nano-radiosensitizers in the radiotherapy for glioma.